2008
DOI: 10.1111/j.1439-037x.2008.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Humidity on Temperature‐Induced Grain Sterility in Rice (Oryza sativa L)

Abstract: High temperature‐induced grain sterility in rice is becoming a serious problem in tropical rice‐growing ecosystems. We studied the mechanism of high temperature‐induced grain sterility of different rice (Oryza sativa L) cultivars at two relative humidity (RH) levels. Four varieties of Indica and Japonica rice were exposed to over 85 % RH and 60 % RH at 36/30 °C, 34/30 °C, 32/24 °C and 30/24 °C day/night air temperatures from late booting to maturity inside sunlit phytotrons. Increasing both air temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(125 citation statements)
references
References 19 publications
6
112
1
6
Order By: Relevance
“…This result was contrary to the previous reports that the increase of vapor pressure deficit reduced high temperature-induced spikelet sterility by increasing transpirational cooling of panicle (Matsui et al, 2007;Jagadish et al, 2007;Weerakoon et al, 2008;Tian et al, 2010;Julia and Dingkuhn, 2013). On the other hands, there was a paucity of studies that low relative humidity under high temperature accelerated rice spikelet sterility induction by desiccating anther and/or pollen.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…This result was contrary to the previous reports that the increase of vapor pressure deficit reduced high temperature-induced spikelet sterility by increasing transpirational cooling of panicle (Matsui et al, 2007;Jagadish et al, 2007;Weerakoon et al, 2008;Tian et al, 2010;Julia and Dingkuhn, 2013). On the other hands, there was a paucity of studies that low relative humidity under high temperature accelerated rice spikelet sterility induction by desiccating anther and/or pollen.…”
Section: Discussioncontrasting
confidence: 93%
“…Further detailed study is needed to verify the effect of VPD on spikelet sterility. Most of recent studies indicated that decreasing VPD under high temperature conditions decreased spikelet fertility (Abeysiriwardena et al, 2002;Matsui et al, 2007;Yan et al, 2008;Weerakoon et al, 2008;Tian et al, 2010;Yan et al, 2010;Julia and Dingkuhn, 2013;Van Oort et al, 2014). However many of these studies were conducted under high relative humidity conditions above 80% and compared with normal condition of 60% relative humidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty hybrids exhibited better performance than the standard check for plant height. These results are in agreement with those obtained by Weerakoon et al (2008), El-Mouhamady (2009) and El-Mouhamady et al, 2013. Positive heterosis was enviable for rest of the traits viz., Productive tillers per plant, Grains per panicle, Root length, Root dry weight, Root: Shoot ratio, Hundred grain weight, , Chlorophyll stability index, Harvest index, Relative water content, Proline content and grain yield per panicle.…”
Section: Resultssupporting
confidence: 93%
“…Koshihikari) by interspecifi c hybridization with a wild rice, O. offi cinalis Wall ex Watt (CC genome), was considerably more effective in mitigating heat-induced spikelet sterility by fl owering in the early morning when the temperature was cooler (Ishimaru et al, 2010). However, further studies were needed to validate the practical importance of the EMF trait for rice cultivation because the effect of microclimates on spikelet sterility is complicated; humidity, wind velocity and CO 2 concentrations negatively affect spikelet sterility (Kim et al, 1996;Matsui et al, 1997a;Matsui et al, 1997b;Weerakoon et al, 2008). Matsui et al (1997b) reported that a wind velocity above 0.85 m s -1 drastically increased spikelet sterility at 37.5ºC, and relative humidity of 60% in a chamber experiment.…”
mentioning
confidence: 99%